Evaluasi Kesesuaian Lahan untuk Tanaman Buah-Buahan Potensial di Kebun Jemaat Negeri Hatu, Kecamatan Leihitu Barat - Rahawarin, Rahul; Risamassu, Robby G; Liubana, Simson (Fakultas Pertanian, Universitas Pattimura, 2024)
This research was conducted in Negeri Hatu at the location of the congregation garden to know the characteristics and quality of land, determine land suitability class, and make a map of the suitability class for fruit plants. This research used a survey method with synthetic and analytical approach patterns with free survey observation distance on land units. The results of the land suitability class assessment for langsat and rambutan plants have a land suitability class (S1) of 0,973 ha or 18.80 percent, S2eh of 1,374 ha or 26.52 percent, S3eh of 1,091 ha or 21.06 percent and for unsuitable classes (N) of 1,744 ha or 12.97 percent. Banana crops: (S1) covering 0,973 ha or 18.80 per cent. S2eh covers 1,374 ha or 26.52 percent, while S3eh covers 1,091 ha or 21.06 percent and unsuitable class (N) covers 1,744 ha or 12.97 percent. Jackfruit plants: (S1) covers 0,973 ha or 18.80 percent. While S2eh covers 1,374 ha or 26.52 percent, while S3eh covers 1,091 ha or 21.06 percent, and for unsuitable class (N) covers 1,744 ha or 12.97 percent. Pineapple plant: ). (S1) is 0.973 ha or 18.80 per cent. While S3eh covers 1,374 ha or 26.52 percent, S3eh covers 3,537 ha or 21.06 percent, and unsuitable class (N) covers 0.001 ha or 0.00 percent.